Antenatal Indomethacin Treatment for Congenital Myotonic Dystrophy - Kyohei Yamaguchi; Hiroaki Tanaka; Fumi H. Furuhashi; Kayo Tanaka; Eiji Kondo; Tomoaki Ikeda (Case Reports in Obstetrics and Gynecology)
Myotonic dystrophy is an autosomal-dominant disorder. Its congenital type is the most severe form, with respiratory failure that can be a life-threatening event after birth. There are no antenatal treatments that can improve neonatal outcomes of myotonic dystrophy. We treated a fetus with congenital myotonic dystrophy by administering indomethacin to the 31-year-old Japanese mother affected by myotonic dystrophy and polyhydramnios. We observed increased fetal breathing movement and a reduction of the amniotic fluid volume. The baby was born at 37 weeks and discharged from the neonatal intensive care unit with a favorable outcome. Indomethacin treatment is likely to improve fetal lung function and to control the amniotic fluid volume. This report emphasizes the importance of further investigations regarding the optimal management of congenital myotonic dystrophy.